Application of Quantitative Susceptibility Mapping in the Assessment of Iron Content in Brain Regions of Normal Children - Tang, Shilong; Zhang, Guanping; Liu, Xianfan; Chen, Zhuo; He, Ling (Current Medical Imaging, 2022)
Purpose: We evaluated brain iron content in a healthy pediatric population using quantitative susceptibility mapping (QSM). Methods: From June 2018 to December 2019, healthy subjects aged 2-18 years old (200 males, 200 females) with no anatomical abnormalities were assessed. All of the children underwent 3D T1 anatomical MRIs in addition to the sequence scans of enhanced T2 star-weighted angiography (ESWAN). The ESWAN sequence images were obtained with software to attain quantitative susceptibility mapping of the entire brain. The magnetic susceptibility values in the same brain region were compared across different age groups. The magnetic susceptibility values expressed in the same age group were compared across sexes, brain sides, and brain regions. Results: The magnetic susceptibility value of each brain region increased with age, and the magnetic susceptibility value expressed by each brain region demonstrated a positive correlation with the children’s age (r=0.63, P<0.05). No dramatic difference in magnetic susceptibility was observed between the brain’s left side and right side in the children within the age range ≥2-<6; however, among the children within the age range ≥6-<18, the magnetic susceptibility values expressed by the left putamen nucleus, globus pallidus, and substantia nigra were higher than those expressed by the same regions on the right side (P<0.05). Conclusion: Quantitative susceptibility mapping can be used to evaluate the content of iron in each brain region of normal children.
Keywords: brain